(untitled) (Contemporary Journal of Social Science Review, 2024)
Second language learning deals with the process of how learners learn a second language or L2 as opposed to their native language or L1. One of the most significant components for learning is the method of instruction that instructors use in and out of the classrooms for the process of second language learning. This research aims to shed light on the best available technological tools and gadgets for different language skills and to explore the consequences of implementation of technology for second language learning. This study explores respondents’ opinions regarding the use of technology for second language/L2 learning inside and outside of the classroom and what technological tools and gadgets are preferable for each language skill. This study suggests that technology-enhanced or smart classrooms have better learning consequences. Technologically enhances engagement, increases learners’ confidence and makes the learning environment conducive. Respondents agreed that use of technology even outside of the classroom also benefits the learners. This research has been conducted following the quantitative method. The data was collected with the help of a questionnaire. Sample is selected randomly from seventy (70) undergraduate students from Lahore city to know their opinion about the use of technology for second language learning both inside and outside of the classroom. The study reveals that technology-based environment boosts students’ confidence, enhances engagement and makes the subject interesting. There are so many technological tools and gadgets that are available for leaning language both inside and outside formal classrooms.